2005
DOI: 10.1007/s10608-005-3166-1
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Parenting Style, Cognitive Style, and Anxiety and Depression: Does Increased Early Adversity Influence Symptom Severity Through the Mediating Role of Cognitive Style?

Abstract: Despite the central role accorded to cognitive style in mediating the relationship between negative parenting and the development of anxiety and depression, few studies have empirically examined this relationship. Using a clinical sample, this study examined the relationship between early experiences with low care, increased control, abuse and neglect, and symptoms of anxiety and depression, via the mediating effects of cognitive style. It was found that individuals who rate their parents as being more abusive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
69
1
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 65 publications
19
69
1
5
Order By: Relevance
“…It is a relatively new instrument. Shah and Waller (40) published preliminary norms for a depressed group, and it has been used in depressed populations (41) as well as with people with an abuse history (42). Schmidt et al (43) showed that its primary scales possess adequate test-retest reliability and internal consistency, with the majority of the proposed scales being replicated by factor analysis.…”
Section: Methodsmentioning
confidence: 99%
“…It is a relatively new instrument. Shah and Waller (40) published preliminary norms for a depressed group, and it has been used in depressed populations (41) as well as with people with an abuse history (42). Schmidt et al (43) showed that its primary scales possess adequate test-retest reliability and internal consistency, with the majority of the proposed scales being replicated by factor analysis.…”
Section: Methodsmentioning
confidence: 99%
“…For example, future studies may examine the influence of other early experiences, such as parental over-control and over-protection or other adverse and uncontrollable events, on the development of distal beliefs and ultimate panic. Prior research, for example, has found a link between low warmth and over-controlling parenting style, cognitive style, and anxiety (McGinn et al 2005). Examining the impact of various childhood experiences on the development of both distal and proximal cognitions, and ultimately panic, would also provide greater confirmation for the various theoretical models encompassed within the unified model of panic.…”
Section: Discussionmentioning
confidence: 95%
“…A large body of research has demonstrated the importance and implications of cognitive vulnerability in the field of depression and other mood disorders (e.g., Abramson et al 2002;Beck 1964Beck , 1987Calvete et al 2013;Cukor and McGinn 2006;Hamilton et al 2013;Ingram et al 1998;McGinn et al 2005). Research has also been conducted to investigate cognitive vulnerability factors in the etiology and maintenance of anxiety disorders (e.g., McGinn et al 2005McGinn et al , 2010Riskind and Williams 2005;Riskind et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ginsburg and Bronstein, 1993;Gottfried et al, 1994;Kellan, 2000;Hoang, 2007; Umo, 2013 H6: Family characteristic positively affects intellectual characteristic of students. Dombusch et al, 1987;McGinn et al, 2005;Houtenville and Conway, 2008;Akinsola, 2011;Wang, 2014 H7: Psychological characteristic positively affects HOTS. Richmond and Serna, 1980;Amabile et al, 1990;Moneta and Siu, 2002;Pannells and Claxton, 2008;Lather et al, 2014 H8: Intellectual characteristic positively affect HOTS.…”
Section: Inclusion Criteriamentioning
confidence: 99%